Education of patients with diabetic foot syndrome and sense of coherence - Rapacz, Agnieszka; Kózka, Maria; Ogarek, Maria (Nursing Problems / Problemy Pielęgniarstwa, 2007)
Introduction. After the diagnosis of diabetic foot syndrome, the patient is expected to make several changes in his daily life that will adjust it to the requirements of therapy. The patient’s readiness to make these changes depends on his knowledge, resources conviction that the changes are justified and possible to implement. Educational programs have to focus on patient’s understanding of the need of changes, his belief in the plausibility of the recommendations and the success of the therapy. Aim. The purpose of the study was to assess the influence of education of the patients with diabetic foot syndrome on their sense of coherence. Material and methods. The study included 84 patients with diabetic foot syndrome and 42 among them participated in education program. The Questionnaire and Questionnaire Live Orientate (SOC-29) were used. Results and conclusions. The results of the study are: deficits in patients’ knowledge, dependence between education and sense of coherence. Higher sense of coherence was obtained in group participating in education program.